Feasible jig for coordinate measuring machine / Aziurah Mohd Shah ... [et al.] - Mohd Shah, Aziurah; Faizal, Muhammad Faez Ammar; Hashim, Siti Mardini; Hashim, Siti Mardini (2022)
The aim of this project is to design a feasible fixturing jig for a Coordinate Measuring Machine (CMM) to easily hold, support and clamp a workpiece. The CMM is one of the precision equipment that uses a probe to measure the dimensions and geometries of a physical workpiece. Currently, the jig used contains several components that can be troublesome if one of the components is missing. The number of components can go as high as hundreds, depending on the size, and shape of the workpiece. Moreover, additional accessories are required to facilitate the measurement of the workpiece consisting of complex geometry. Therefore, the objective of the design is to reduce the number of jig components and increase the flexibility of the jig to hold a complex workpiece without being required to change any components. According to the feedback acquired from customer surveys, interviews and benchmarks, three designs of the jig; designs 1, 2 and 3 have been evaluated using conceptual selection. Design B is selected as the definitive design, based on the evaluation result in the selection process by using the screening method. The result shows that design B gave the highest net score. The selected design is drawn and analyzed using SolidWorks software. PLA is selected as a material and undergoes the 3D printing process to produce the final product. In conclusion, a cheap and feasible fixturing jig is produced to facilitate the measurement of a specific workpiece.